Evaluación geotécnica de la cantera Llicllao en la construcción de una carretera en Pasco - Ariza Flores, Victor Andre (2023)
The present research article addresses the problems presented in the construction of the Oyón - Ambo Highway located in the Pasco region, in which there was a considerable deficit of hill quarry material for embankments and structural fills. The purpose of the research was to study the physical and mechanical properties of the material from the Cerro de Llicllao quarry located in the Pasco region and to determine the technical feasibility for use in embankments and structural fills for the construction of the Oyón Ambo highway during the restart of construction activities immediately after the social immobilization decreed by the Government to combat the COVID-19 pandemic. The research has a quantitative approach of the applied type. Likewise, it is of the explanatory type because it identifies and solves the cause of the phenomenon; Finally, it has an experimental design specifically of the quasi-experimental type. The results of the investigation show that the Llicllao quarry can be used in the fill and embankment items for the construction of the highway.